Global Change Sharpens the Double-Edged Sword Effect of Aquatic Alien Plants in China and Beyond - Wu, Hao; Ding, Jianqing (Frontiers in Plant Science, 2019)
Many alien aquatic plants are deliberately introduced because they have economic, ornamental or environmental values; however, they may also negatively affect aquatic ecosystems, by blocking rivers, restricting aquatic animals by decreasing dissolved-oxygen, and reducing native biodiversity. These positive and/or negative ecological effects may be enhanced under global change. Here, we examine the impacts of global change on aquatic alien plant introduction and/or invasions by reviewing their introduction pathways, distributions and ecological effects. We focus on how climate change, aquatic environmental pollution and China’s rapid economic growth in recent decades affect their uses and invasiveness in China. Among 55 species of alien aquatic plants in China, 10 species are invasive, such as Eichhornia crassipes, Alternanthera philoxeroides and Pistia stratiotes. Most of these invaders were intentionally introduced and dispersed across the country but are now widely distributed and invasive. Under climate warming, many species have expanded their distributions to areas where it was originally too cold for their survival. Thus, these species are (and will be) considered to be beneficial plants in aquaculture and the restoration of aquatic ecosystems (for water purification) across large areas. However, climate warming is (and will be) increasing their invasion risk in more areas. In addition, nitrogen deposition and phosphorus inputs may also alter the status of some alien species. Furthermore, climate warming has shifted the interactions between alien aquatic plants and native plants and herbivores, thus impacting aquatic communities and ecosystems. Under climate change, more precipitation in North China and more frequent flooding in South China will increase the uncertainties of ecological effects of alien aquatic plants in these regions. We also predict that, under the continuing booming economy in China, more and more alien aquatic plants will be used for aquatic landscaping and water purification. In conclusion, our study indicates that both human activities under rapid economic growth and climate change can either increase the potential uses of alien aquatic plants or make the aquatic invaders worse in China. These findings are critical for future risk assessment of aquatic plant introduction and aquatic ecosystem restoration.